2015
DOI: 10.1103/physrevb.92.224432
|View full text |Cite
|
Sign up to set email alerts
|

Shapiro steps for skyrmion motion on a washboard potential with longitudinal and transverse ac drives

Abstract: We numerically study the behavior of two-dimensional skyrmions in the presence of a quasi-onedimensional sinusoidal substrate under the influence of externally applied dc and ac drives. In the overdamped limit, when both dc and ac drives are aligned in the longitudinal direction parallel to the direction of the substrate modulation, the velocity-force curves exhibit classic Shapiro step features when the frequency of the ac drive matches the washboard frequency that is dynamically generated by the motion of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 66 publications
2
26
0
Order By: Relevance
“…Simulation and system-We consider a 2D simulation with periodic boundary conditions in the x and ydirections using a particle-based model of a modified Thiele equation recently developed for skyrmions interacting with random [21,23] and periodic [30,40] pinning substrates. The simulated region contains N skyrmions, and the time evolution of a single skyrmion i at position r i is governed by the following equation:…”
Section: Introductionmentioning
confidence: 99%
“…Simulation and system-We consider a 2D simulation with periodic boundary conditions in the x and ydirections using a particle-based model of a modified Thiele equation recently developed for skyrmions interacting with random [21,23] and periodic [30,40] pinning substrates. The simulated region contains N skyrmions, and the time evolution of a single skyrmion i at position r i is governed by the following equation:…”
Section: Introductionmentioning
confidence: 99%
“…The position of an isolated magnetic skyrmion can be manipulated by an external driving force. A spinpolarized electric current has been reported to be an effective driving force for the motion of magnetic skyrmions in confined geometries [14,21,22,[39][40][41]. In addition, the scattering of a propagating spin wave has been demonstrated to generate a momentum transfer, resulting in a skyrmion or domain wall motion [42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Magnus effects are known to be important for skyrmions in chiral magnets, where the ratio of the Magnus term to the damping term can be ten or higher [12][13][14][15][16][17]. Skyrmions can be set into motion by an applied spin-polarized current, and the Magnus term has been shown to strongly affect the interaction of the moving skyrmions with pinning sites, leading to reduced depinning thresholds [14-16, 18, 19], a drive dependent skyrmion Hall angle [19][20][21][22], and skyrmion speed up effects [20,21].Recent studies of skyrmions driven over a periodic q1D substrate by a dc drive that is parallel to the substrate periodicity direction combined with a perpendicular ac drive showed that a new class of Magnus-induced Shapiro steps arises due to an effective coupling by the Magnus term of the perpendicular and parallel particle motion, whereas in the overdamped limit no Shapiro steps occur for this drive configuration [23]. Here we examine skyrmions confined to a 2D plane containing a q1D periodic substrate and moving under the influence of a dc drive applied perpendicular to the substrate periodicity direction along with a parallel or perpendicular ac drive, and we find that a rich variety of dynamical phases can occur.…”
mentioning
confidence: 99%
“…We map the evolution of the dynamic phases as a function of ac drive amplitude and the ratio of the Magnus to the damping term. In addition to their interest as signatures of a new dynamical system, these results could be important in providing a new way to precisely control the direction of motion of skyrmions in order to realize skyrmion-based memory or logic devices [28].Simulation-We model a 2D system with periodic boundary conditions in the x and y directions containing a q1D substrate and a skyrmion treated with a particlebased model that has previously been used to examine driven skyrmion motion in random [18,19], 2D periodic [21], and 1D periodic substrates [23,29]. The skyrmion dynamics are determined using the following equation of…”
mentioning
confidence: 99%